Saberes elementares aritméricos no ensino primário em Sergipe (1890 a 1944) - Rocha, Wilma Fernandes (2016)
In this paper, it is presented the result of an investigation that aimed to analyze basic arithmetical knowledge for primary education in Sergipe, in official documents, in the period from 1890 to 1944. In order to achieve the original intent, documents were located and examined such as: Primary Public Instruction Regulations, Education Programs, Reports on School Groups, State Presidents messages and Teaching Manuals. The theoretical contribution came from the use of authors such as Valente (2013), Bloch (2002) and Chartier (2002). The documents examination was guided by the understanding of arithmetical elementary knowledge inspired by Valente (2015), which later went through a refinement from evidences identified in Messages and Reports that pointed out the manuals Elementary Arithmetic by Antonio Trajano and Lessons of Things by Calkins which were taken as a reference to identify arithmetical elementary knowledge that can be listed as it follows: numbers, arithmetic operations and problems, fractions and their operations, divisibility, proportion, simple interests and measures. References materials as mechanical counters were identified, Parker‘s cards and statement to be adopted the book Elementary Arithmetic for the teaching of elementary arithmetic knowledge. It was possible to identify principles adopted by Calkins (1886/1950), which went through steps such as: imagination, judgment, observation, consequently, to the comparison and classification, in order to get into knowing elementary arithmetical knowledge prescribed in Teaching Programs in Sergipe. For instance, regarding to the knowledge of Arithmetic Operations, in adding up, the manual suggested using mechanical counter as it follows: adding spheres up to ten spheres and two spheres. In the 1917 Program, it should take the decimal place up to twelve, meaning, in both they should make the sum up to twelve. The method indicated for primary education was the intuitive until the 1920s, with change indications for what advocated the principles of the New School since then and with greater emphasis after the 1930s.